Reprints of Rare Papers on Mollusca: Bryant Walker (1918) Synopsis and Classification, Concluded (Continued from Sterkiana 45) - Bryant Walker (Hello World!, 1972)
With this installment of Walker's Synopsis and Catalogue, reprinting of this work is complete. A title page precedes page 171 and a few notes will appear in the next number of STERKIANA explaining the extraneous material that has crept into the reprint.